The abandonment of landownership: a proposed model for regulated exit - Cramer, Richard Henry (Department of Private Law, 2021)
The question whether it is possible to abandon landownership is unresolved in South African law. The subject has only rarely been the subject of attention by scholars, with legislation and existing case law providing little in the way of clear guidance. This lack of clarity is obviously not ideal. In South Africa landowners may find themselves burdened with the ownership of land which has accrued a negative value. This thesis seeks to engage with the question on a theoretical level, including to provide answers to practical problems in the South African landownership context. Ultimately two primary questions must be answered: 1. Is the abandonment of landownership possible in the South African legal framework? 2. Should the abandonment of landownership be permitted, and if so, under what circumstances? The first question is evaluated in light of existing common-law principles, case law, as well as legislation such as the Deeds Registries Act 47 of 1937. However, the second question will be the primary focus of the thesis. Through the lens of the socialobligation norm of property as conceptualised by Gregory Alexander, as well as comparative studies of Swiss and Scots law, the thesis explores the viability of a right to abandon landownership in South African law. The thesis argues that the abandonment of landownership in South Africa is not possible in the prevailing legal framework. Furthermore, an unrestricted right to abandon is not viable in the South African socio-economic context. However, landowners who find themselves burdened with land which has accrued a negative value for which they are not at fault may require some form of regulated exit from that ownership. The thesis makes suggestions for legislative law reform in this regard, to provide balance between the interests of landowners and the wider community.